Programmable gain amplifier - Wong, Zhen Lin (2014)
A CMOS fully differential programmable gain amplifier (PGA) has been designed for RF receiver. It uses binary weighted switching techniques to allow switching of gain a various steps. This configurations consist of four differential pair input which reduces common noise and four active load which will help in getting the desired gain with the formula of gmRL. These four stages of gain will form the 24 (16 steps) gain steps while the most significant bit will deduce if it is a positive or negative gain. Thus, completing a 5 bits (32 steps) programmable gain amplifier. It also includes a common mode feedback to help obtain desired DC output at a particular voltage depending on the input common mode requirement of the next stage. The gain of PGA varies from -24dB to 24dB with respect to the input reference. It also has an operating bandwidth greater than 14MHz. It consumes about 1.1mW total power and has 1dB compression point of -2.3dBm. IIP3 was also found to be around 2.4dBm. All results are achieved with differential pair and load in saturation region instead of sub-threshold region which provide high level of gain. This circuit is designed base GlobalFoundries 65nm CMOS technology.